Latin America in Its "Gramscian Moment". the Limitations of a "New European Social Democracy"-Style Exit to This Impasse - Palma-Penco, J (FONDO CULTURA ECONOMICA, 2020)
Latin America is trapped in a "Gramscian Moment", when the old fades, but the new fails to be born. In this interregnum, as Gramsci warned us, it is almost inevitable that "a wide variety of harmful symptoms will appear". It is as if the Macbeth witches had prophesied to us: you will live bogged down between a neoliberal model that lost all legitimacy and progressive discourses that fail to generate enough credibility. Economically, this means that along with having to face the pandemic, we also have to challenge one of the endemic illnesses in the region: the lack of imagination in matters of economic policy. The former wreaks havoc, creating challenges until recently unimaginable, which inevitably collide with the obstacles posed by the latter. And so we continue to sink into the quicksand of inertia; meanwhile, the anxiety (in many the panic) of a disorderly exit from the crisis leads some to idealize a "new European social democracy"-style solution. That is, as long as we do not touch either the rentier structure of accumulation or that of taxation, some extra social protection would be welcomed (if financed, of course, with debt rather than taxes) in order to guarantee a minimum of social peace and a hint of equity. In other words, as in the lyrics of the Hotel California song: "We are all just prisoners here, of our own device"-and we still can t think of a way to break our chains-. The great challenge of this historical moment is to free our social imagination.